(untitled) (International Journal of Engineering and Computer Science, 2025)
This article examines the theoretical foundation and implementation features of Zero Trust Architecture (hereafter referred to as ZTA) for scalable web and mobile solutions. It substantiates the necessity of moving away from traditional perimeter-based security models in favor of dynamic strategies capable of providing reliable protection for distributed and hybrid systems. The practical section of the study demonstrates how modern identity management tools (Azure Active Directory, Conditional Access, MFA, passwordless authentication), microsegmentation technologies (VNet, NSG, cloud firewalls), and continuous monitoring systems (Azure Sentinel, AI-based analytics) can mitigate the risk of unauthorized access and insider attacks. The proposed ZTA implementation stages, from preliminary infrastructure auditing to continuous change management, confirm the practical effectiveness of the model and its significance for modern web and mobile solutions. The findings are highly relevant for organizations seeking to counter modern cyber threats and ensure the stable operation of information systems. The presented data is of interest to cybersecurity researchers, distributed system architects, and leading information security specialists aiming to integrate Zero Trust concepts into scalable web and mobile solutions through an in-depth analysis of both theoretical foundations and practical implementation methodologies.